The Evaluation of Mathematical Communication Skills with Moodle-assisted CTL Learning Model in Middle School (Universitas Negeri Semarang, 2022)
Mathematical communication skills are the ability to identify and write everyday problems into mathematical language. One way to improve mathematical communication skills is to apply Moodle-assisted CTL learning. This study is written to analyze and evaluate mathematical communication skills improvement of the students taught by moodle-assisted CTL learning model. The research design used is experimental research with Pre-Experimental Design. The samples of this research are students of class VIII A at SMP Negeri 22 Semarang. The research data is obtained using a mathematical communication ability test. The data analysis in this study are; (1) Right Side Proportion Test; (2) Average difference Test; (3) N-Gain Test. The results of data analysis in this study are interpreted as follows: (1) students' mathematical communication skills in Moodle-assisted CTL learning are classically complete (Z_count>Z_table; 1.66 > 1.64); (2) mathematical communication skills in CTL learning assisted by Moodle have completed the minimum completeness criteria (t_count>t_table; 5.55 > 1.72); (3) there is an average increase in students' mathematical communication skills between before being given Moodle-assisted CTL learning and after Moodle-assisted CTL learning with N-Gain of 0.57. So we can conclude that students' mathematical communication skills have improved during the application of the moodle-assisted model, and we can suggest that the moodle-assisted CTL learning model can be used to improve mathematical communication skills.